Metode Pemahaman bagi Penelitian Antropologi - Ninuk Kleden-Probonegoro (Antropologi Indonesia, 2006)
Amidst the many changes in the approaches taken by anthropologists today, the author reexamines the works produced in the more humanistic tradition of anthropology. She begins with the question of whether anthropological research can be conducted with an idiographic approach. Through a discussion of Verstehen, experience and hermeneutics, and drawing from her own experiences in the field, the author argues that the methods characteristic of amore humanistic anthropology can be applied to anthropological research and remain scientifically sound. Key words: hermeneutic; experience; "thick description".